2018
DOI: 10.1186/s12885-018-4853-0
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1/PD-1 crosstalk in colorectal cancer: are we targeting the right cells?

Abstract: BackgroundThe analysis of tumour-infiltrating immune cells within patients’ tumour samples in colorectal cancer (CRC) has become an independent predictor of patient survival. The tumour microenvironment and the immune checkpoints, such as PD-L1/PD-1, are relevant to the prognoses and also appear to be relevant for further CRC therapies.MethodsWe analysed the presence and features of the infiltrated monocyte/macrophage and lymphocyte populations in both tumour and peritumour samples from patients with CRC (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Furthermore, PD‐L1 inhibition not only blocked the expression of PD‐L1 on the membrane of CRC cells but also restricted the binding activity with PD‐1 in T cells in the tumor microenvironment, thereby avoiding the identification of cancer cells by the immune system and the activation of the immune system (Cantero‐Cid et al, 2018; Dosset et al, 2018). According to the findings of Cioffi et al PD‐L1 was downregulated in response to the transfection of miR‐93 mimics, suggesting the modulatory role of miR‐93 in the immune evasion of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, PD‐L1 inhibition not only blocked the expression of PD‐L1 on the membrane of CRC cells but also restricted the binding activity with PD‐1 in T cells in the tumor microenvironment, thereby avoiding the identification of cancer cells by the immune system and the activation of the immune system (Cantero‐Cid et al, 2018; Dosset et al, 2018). According to the findings of Cioffi et al PD‐L1 was downregulated in response to the transfection of miR‐93 mimics, suggesting the modulatory role of miR‐93 in the immune evasion of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…When M2-TAMs was depleted, there was a marked increase in the numbers of CD4+ and CD8+ TILs in melanomas [8]. In colorectal cancers, high expression of CD163 on TAMs was found in TME, resulting in an increased number of CD4+ lymphocytes that contributed to up-regulate the PD-1 expression [23]. Moreover, M2-TAMs produced tumor-promoting cytokines, such as interleukin (IL)-6 and IL-10, which suppress cytotoxic TIL [8,23].…”
Section: Discussionmentioning
confidence: 99%
“…In colorectal cancers, high expression of CD163 on TAMs was found in TME, resulting in an increased number of CD4+ lymphocytes that contributed to up-regulate the PD-1 expression [23]. Moreover, M2-TAMs produced tumor-promoting cytokines, such as interleukin (IL)-6 and IL-10, which suppress cytotoxic TIL [8,23]. These tumor prone macrophages could express the transcription factor IRF4 [23], which promoted CD8+ T cell exhaustion and acts as an up-regulator of PD-1 expression [24].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown the high expression of PD-1 in MSI-H tumors, thus providing the evidence for including its immunohistochemical expression as a predictive marker [36,37]. PD-L1 (Programmed Death Ligand-1 receptor) or CD274 is expressed on the surface of certain activated immune components, such as B cells, T cells and NK cells CD14+-TAMs, and on the surface of cancer cells [98,99]. The interaction between PD-1 and PD-L1 leads to the inhibition of T cell activation and reduces pro-inflammatory cytokine secretion (INF-γ, TNF-α and IL-2).…”
Section: Therapeutic Approaches For Avoiding Immune Evasion In Sacmentioning
confidence: 99%